Attentional selection and word processing in Stroop and word search tasks: the role of selection for action. - Brown, Tracy L. (American Journal of Psychology)
The role of selection for action was investigated by having subjects carry out two tasks, differing in whether words were selected for action, on identical displays. The identification displays consisted of square color patches appearing at fixation with either two, four, or eight flanking words being exhibited at any of the eight sides and corners. The subjects carried out either a Stroop color-naming task or a word search task requiring detection of a color name among the flanking words. This was done by a manual presence/absence response in experiment one and by a vocal naming response in experiment two. Evidence from the word search task supported serial, self-terminating search requiring allocation of spatial attention, whereas the color-naming task produced Stroop effects and thus signaled parallel word processing in multiword displays.